Association of Gene Growth Hormone (GH) Diversity with Quantitative Characteristics of Crossing Merawang Chickens with Arabic Chickens - Muhammad, Mus'ab; Depison; Gushairiyanto; Harahap, Ratna Sholatia (Faculty of Animal Science, Universitas Brawijaya, 2025)
The growth hormone (GH) gene plays a crucial role in regulating the growth and metabolism of Chickens. This study investigates the polymorphism of the GH gene and its association with growth traits in chickens resulting from the crossbreeding of Merawang and Arabs (MeA). The research began by raising 60 chickens—30 males and 30 females—from the Merawang and Arabic chicken cross for four months. Various growth traits, including weight, weight gain, and body size, were measured. Blood samples from the MeA chickens were collected for DNA analysis to assess GH gene polymorphism. The analysis involved DNA extraction, PCR amplification, and RFLP using the Taql enzyme. The data were analysis using T-test to evaluate the association of the GH gene polymorphism with growth traits. The results showed that the male of crosses between Merawang and Arab chicken (MeA) have higher significant (P<0.05) growth traits, including body weight, weight gain, and body size than female MeA chickens. The chest circumference is a defining characteristic of body size in male and female MeA chickens, while the upper body length is a crucial feature of body shape. The GH gene were found polimorpic with three genotypes, including GG, AG, and AA. The GH gene polymorphisms have a significant association (P<0.05) with growth traits, including body weight, body weight gain, and body size. Chicken with GG genotype have a higher growth trait than others. The GH gene can be used as a potential genetic marker for selection for improving chicken growth.